PENDEKATAN PEKERJAAN SOSIAL Relevansi dan Kontribusinya dalam Pembangunan Sosial - Suradi Suradi (Politeknik Kesejahteraan Sosial, 2007)
The social problems these days are so complex that it is impossible to solve it only by one elimensional approach since this approach is actually not for used on solving the problems.To solve then social problems, we need to develop multi dimensional approach. Social workers provide that approach. In general, social workers provide social intervansion which is focused on problem solving which implement various approaches comprehensively (from various perspectives). In this generalist model, social intervension is supported by social workers basic system which work sinergicallyKey Words : social work and social welfare, social problem, social development.